2011
DOI: 10.1530/rep-11-0280
|View full text |Cite
|
Sign up to set email alerts
|

Pre-natal social stress and post-natal pain affect the developing pig reproductive axis

Abstract: This study assessed the effect of pre-natal social stress and post-natal pain on the reproductive development of young (approximately day 40) pigs. Male pigs carried by sows that were stressed by mixing with unfamiliar older sows for two 1-week periods during mid-pregnancy had lower plasma testosterone (0.54 vs 0.86 ng/ml, S.E.D.Z0.11; PZ0.014) and oestradiol (E 2 ; 22.9 vs 38.7 pg/ml, S.E.D.Z7.80; PZ0.021) concentrations compared with males carried by unstressed control sows. Although there was no effect of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Limited evidence from studies in pigs indicates that prenatal exposure of pregnant sows to social stress may also affect the development of the reproductive axis in the male and female offspring (Ashworth et al 2011). In pre-pubertal females, prenatal stress significantly reduces the number of primordial follicles in the ovaries (Ashworth et al 2011).…”
Section: Effects On the Reproductive Axis And Reproductive Behavioursmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited evidence from studies in pigs indicates that prenatal exposure of pregnant sows to social stress may also affect the development of the reproductive axis in the male and female offspring (Ashworth et al 2011). In pre-pubertal females, prenatal stress significantly reduces the number of primordial follicles in the ovaries (Ashworth et al 2011).…”
Section: Effects On the Reproductive Axis And Reproductive Behavioursmentioning
confidence: 99%
“…In pre-pubertal females, prenatal stress significantly reduces the number of primordial follicles in the ovaries (Ashworth et al 2011). The long-term effects of this are unclear; however, studies in women indicate that the ovarian follicle pool may predict reproductive capacity in later life.…”
Section: Effects On the Reproductive Axis And Reproductive Behavioursmentioning
confidence: 99%
“…Various experimental studies conducted on mice, rats, and pigs showed that many environmental and ethological prenatal stressors can have injurious effects on the pregnancy and early and long-term adverse effects on the offspring. Different prenatal treatments and stress types, such as medications [1], drinking water restriction and deprivation [2][3][4], feed restriction [5], immobilization [6,7], light intensity [8], stocking density [9], restraint or social stressors [10][11][12][13][14][15][16], heat or noise [17], to which a pregnant female is exposed, can affect pregnancy outcome and influence many aspects of physiological systems in the offspring including sexual behavior, puberty onset, gonad function, reproductive hormones, and development of the reproductive organs.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal gestational stress and housing can alter female pigs' puberty (O'Gorman et al, 2007;Estienne and Harper, 2010) and reduce ovarian follicles (Ashworth et al, 2011) and litter size (Jarvis et al, 2006). In male pigs, it can reduce anogenital distance (Lay et al, 2008), a biomarker for fetal androgen exposure during sexual differentiation, and postnatal reproductive hormone concentrations (Ashworth et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research by Ashworth et al (2011) demonstrated that midgestation maternal social stress can influence postnatal testosterone concentration and testicular steroidogenic enzyme expression. However, midgestation maternal heat stress and crowding did not affect testosterone concentrations of pubertal boars (Kattesh et al, 1979).…”
mentioning
confidence: 96%